2011
DOI: 10.1007/s12613-011-0499-5
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum matrix composites reinforced by molybdenum-coated carbon nanotubes

Abstract: To extend the application of carbon nanotubes (CNTs) and explore novel aluminum matrix composites, CNTs were coated by molybdenum layers using metal organic chemical vapor deposition, and then Mo-coated CNT (Mo-CNT)/Al composites were prepared by the combination processes of powder mixing and spark plasma sintering. The influences of powder mixing and Mo-CNT content on the mechanical properties and electrical conductivity of the composites were investigated. The results show that magnetic stirring is better th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…Similarly, it is shown that there is no intermetallic formation in the microstructure of (Mo-coated CNT)-Al nanocomposites [16]. It is attributed to the presence of Mo layer, acting as an appropriate barrier to the interfacial reaction between CNTs and the matrix.…”
Section: Metallizationmentioning
confidence: 92%
See 3 more Smart Citations
“…Similarly, it is shown that there is no intermetallic formation in the microstructure of (Mo-coated CNT)-Al nanocomposites [16]. It is attributed to the presence of Mo layer, acting as an appropriate barrier to the interfacial reaction between CNTs and the matrix.…”
Section: Metallizationmentioning
confidence: 92%
“…Moreover, the inhomogeneous dispersion of CNTs gives rise to non-homogeneity and anisotropy in these binary systems. On the other hand, it may impede the full sintering and reduces the relative density, wettability of CNTs, and resultant mechanical properties [16,[33][34][35].…”
Section: Dispersion Of Cnts Into Metallic Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…In an attempt to improve CNT dispersion and interfacial contacts in an Al matrix, Nie et al coated the nanotubes with molybdenum. [8] According to the authors, this did not improve the electrical conductivity of the composites due to low CNT and Mo conductivities (compared to Al) and most probably, due to porosity (up to 5%). In electroless-deposited spark-plasma-sintered (SPS) MWCNT/ Cu composites, the increase in the electrical resistivity was significant.…”
Section: Introductionmentioning
confidence: 96%